Risk factors associated with childhood tuberculosis: a case control study in endemic tuberculosis area - Zuraida, Zia Faizaty; Wijayanti, Siwi Pramatama Mars (International Journal Of Community Medicine And Public Health, 2018)
Background: Tuberculosis (TB) in childreen is still considered as important public health problems in various countries, including Indonesia. Risk factors related to childhood tuberculosis is crucial to identify in order to conduct prevention effort effectively. The purpose of this research is to determine the effect of environmental health in house, contact history and nutritional status toward childhood tuberculosis. Methods: This research is an analytical observational study using case-control design, with 35 samples of the case and 35 samples of the control. Several variables such as house environment, contact history and nutritional status were obtained by questionnaire and observation in house of respondents. Data analysis was conducted using Logistic Regression test to determine correlation between independent and dependent variables. Results: This research highlighted that contact history and nutritional status were correlated with childhood tuberculosis. While house environment variables such as lighting level, floor type, house occupancy density were not related to the incidence of tuberculosis in children. Conclusions: Contact history and nutritional status were the factors which determined childhood tuberculosis in Banyumas. It is important for parents to maintain good nutritional status of their children and to avoid them from contact with tuberculosis patients.